The impact of limb symmetry on stroke-to-stroke movement variability in para-swimmers during an adapted aerobic step test - Slopecki, M.; Clément, J.; Charbonneau, M.; Côté, J. N. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The study purpose was to measure effects of anthropometric limb characteristics on fatigue-related changes in stroke-to-stroke motor variability (MV) of trunk mediolateral (ML) acceleration. Six Paralympic swimmers performed an in-water, fatiguing, freestyle aerobic test consisting of 5 steps of 200m (n = 4); 150m (n = 1) or 100m (n = 1) with a sacrum worn inertial measurement unit. Upper-limb segment lengths were measured, and symmetry indices (LSI) were calculated. Sample entropy (SampEn) and fractal dimension (FD) were calculated on ML acceleration. Fatigue was confirmed with increased RPE (p < 0.01). ANOVA fatigue response models of SampEn and FD improved with LSI as a covariate (p < 0.01), showing that symmetry indices affected individual responses to fatigue. Coaches should consider anthropometric symmetry when designing para-swimming training plans.